Role of chest ultrasonography in the diagnosis of the causes of acute respiratory failure - Nourane Y Azab; Rabab A El Wahsh; Mohammed E Ammar; Amal A El-Koa (Egyptian Journal of Chest Disease and Tuberculosis, 2022)
Objective To evaluate the role of chest ultrasonography (US) in diagnosing the causes of acute respiratory failure (ARF). Background ARF is a common critical problem and can arise from many diseases. Several modalities such as chest radiograph, US, and computed tomography (CT) scan are being used to diagnose and detect the causes of ARF. Patients and methods The study included 50 patients with ARF admitted to the ICU of Menoufia University Hospital and ICU of Kafr El-Sheikh Chest Hospital. We compared between chest radiograph, chest US, and CT as diagnostic tools to detect the etiology of ARF. Results The sensitivity, specificity, positive predictive value, and negative predictive value and accuracy of lung US in the detection of chest disorders causing ARF were 93.7, 50, 97.8, 45, and 92%, respectively, compared with chest CT as a gold-standard Bedside Lung Ultrasonography in Emergency department protocol was used in the diagnosis of different causes of ARF. Lung US was free in 6% of patients, A profile was found in 12%, A’ profile was found in 2%, A’ profile with anechoic area or hypoechoic area in 6%, B profile was found in 12%, B’ profile in 12%, B’ profile with anechoic area or hypoechoic area in 32%, A/B profile in 6%, no color sign was found in 10%, and hypoechoic simple effusion in 2% of selected patients. Conclusion Chest US is a reliable, quick, bedside, low-cost, noninvasive, and nonionizing imaging tool for early detection of chest-disease causes of ARF.